ANALYSIS OF INTERNAL CAPABILITIES BASED ON RESOURCE-BASED VIEW (RBV) AND VALUE CHAIN IN MAINTAINING THE EXISTENCE OF TRANSPORTATION SERVICE BUSINESS: CASE STUDY OF PT BLUE BIRD TBK - Jeni Kamase; Ackhriansyah Ahmad Gani; Muthia Indah Permatasari; Andi Muh Adib Asharil; Muh. Farhan Firman (STMIK Indonesia Banda Aceh, 2026)
Digital disruption in the land transportation industry requires conventional business players to optimize internal capabilities to survive amid the penetration of app-based services (ride-sharing). This study aims to analyze the internal strategy of PT Blue Bird Tbk. in identifying core competencies and formulating strategies to maintain a competitive advantage. The approach used is the Resource-Based View (RBV) with the VRIO framework (Value, Rarity, Inimitability, Organization) and Value Chain Analysis. The research method uses descriptive qualitative with secondary data collection through annual reports, corporate sustainability reports, and previous scientific literature reviews. The results of the Value Chain analysis show that Blue Bird creates superior value added in operational activities (standardization of independent fleet maintenance) and human resource management (driver training and welfare systems). Furthermore, the VRIO analysis reveals that brand equity regarding safety and comfort aspects, exclusive lounge networks (such as in airports and star-rated hotels), and driver service culture are strategic resources that meet the criteria for a sustainable competitive advantage. The identified internal weakness is the high operational overhead costs of the physical fleet compared to digital asset-light competitors. This study suggests strengthening digital ecosystem integration (super-apps) and diversifying into last-mile logistics services to reduce internal inefficiencies.